2002
DOI: 10.1266/ggs.77.227
|View full text |Cite
|
Sign up to set email alerts
|

Novel endonuclease in Archaea cleaving DNA with various branched structure.

Abstract: We identified a novel structure-specific endonuclease in Pyrococcus furiosus. This nuclease contains two distinct domains, which are similar to the DEAH helicase family at the N-terminal two-third and the XPF endonuclease superfamily at the C-terminal one-third of the protein, respectively. The C-terminal domain has an endonuclease activity cleaving the DNA strand at the 5'-side of nicked or flapped positions in the duplex DNA. The nuclease also incises in the proximity of the 5'-side of a branch point in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 59 publications
3
77
0
1
Order By: Relevance
“…We propose that Mph1 stimulates the endonuclease Mms4/Mus81, since we found an epistatic relationship of mms4 and mus81 to mph1 in terms of sensitivity to camptothecin. Further circumstantial support comes from the findings that in the Mph1 archaeal homologue, Hef, the N-terminal helicase stimulates the endonucleolytic activity of the C-terminal domain (Komori et al, 2002). Proper resolution via Mms4/Mus81-Mph1 would allow replication restart ( Figure 6D).…”
Section: Mph1 Is Likely To Have a Role In Recombinational Dna Repair mentioning
confidence: 98%
See 3 more Smart Citations
“…We propose that Mph1 stimulates the endonuclease Mms4/Mus81, since we found an epistatic relationship of mms4 and mus81 to mph1 in terms of sensitivity to camptothecin. Further circumstantial support comes from the findings that in the Mph1 archaeal homologue, Hef, the N-terminal helicase stimulates the endonucleolytic activity of the C-terminal domain (Komori et al, 2002). Proper resolution via Mms4/Mus81-Mph1 would allow replication restart ( Figure 6D).…”
Section: Mph1 Is Likely To Have a Role In Recombinational Dna Repair mentioning
confidence: 98%
“…biochemical data suggesting that the Mph1-like and Mus81-like domains of archaeal Hef protein cooperatively resolve stalled replication forks (Komori et al, 2002), prompted us to investigate the genetic interaction between mph1 and mms4-mus81 mutations for sensitivity to DNA damaging agents. As previously reported (Bastin-Shanower et al, 2003), we observed mms4 and mus81 single mutants to be sensitive to MMS, 4-NQO and camptothecin ( Figure 3C, D).…”
Section: Genetic Interactions Of Rad54 and Mms4-mus81 With Mph1mentioning
confidence: 99%
See 2 more Smart Citations
“…Hef was originally described in archaebacteria as a protein that could process blocked DNA replication forks into double-strand DNA breaks (Komori et al 2002). Meetei et al (2005) identified the human ortholog of Hef as a 250-kDa component of complex 1 using coimmunoprecipitation experiments.…”
Section: Fancm Is the Mammalian Ortholog Of Hefmentioning
confidence: 99%